PERANCANGAN DAN PEMBUATAN GENERATOR VAN DE GRAAFF ALTERNATIF SEBAGAI MEDIA PEMBELAJARAN FISIKA PADA KONSEP LISTRIK STATIK - Zulirfan, Zulirfan; Eka Putri, Suhefni; Sudrajat, Hendar (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
The purpose of this research was to make learning media in a kind of Van de Graaff Generator to explain the static electric concept. The stages of this research were designing, making, and testing the effectiveness of Van de Graaff Generator. The making of Van de Graaff generator used simple devices and materials that have already available in local market, such as steel ball, electric motor, elastic belt, metal brush, and DC power supply. The testing was done qualitatively and semi qualitatively to the contents of the ball by measuring the voltage of the ground-ball. The maximum voltage ball is 942V which was produced from entry voltage on the strengthener series 6V, with the motor voltage 18V. The Van de Graaff generator can be made as learning media because can prove the existence of gathered charges at the bal